2014
DOI: 10.1126/scitranslmed.3007965
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity of Paclitaxel in Breast Cancer Is due to Chromosome Missegregation on Multipolar Spindles

Abstract: The blockbuster chemotherapy drug paclitaxel is widely presumed to cause cell death in tumors as a consequence of mitotic arrest, as it does at concentrations routinely used in cell culture. However, we determine here that paclitaxel levels in primary breast tumors are well below those required to elicit sustained mitotic arrest. Instead, cells in these lower concentrations of drug proceed through mitosis without substantial delay and divide their chromosomes on multipolar spindles, resulting in chromosome mis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
312
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 331 publications
(362 citation statements)
references
References 51 publications
26
312
1
2
Order By: Relevance
“…It is believed that this kind of event, evoked by paclitaxel, may occur more frequently in vivo due to the fact that a tumor is formed with a complex structure of different types of cells and tissues, which provides cancer cells with a protective environment. Although the concentration of paclitaxel treated in vitro was much lower than that of its plasma concentration in patients (80-280 nM), it is thought that the intracellular concentration of paclitaxel accumulated in MDA-MB-231 cells in vitro and in a tumor are similar, in view of a study conducted by Zasadil et al (7). Since MDA-MB-231-JYJ cells, the small round cells that survived treatment with paclitaxel, were much more proliferative and tumorigenic than MDA-MB-231 cells (Fig.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…It is believed that this kind of event, evoked by paclitaxel, may occur more frequently in vivo due to the fact that a tumor is formed with a complex structure of different types of cells and tissues, which provides cancer cells with a protective environment. Although the concentration of paclitaxel treated in vitro was much lower than that of its plasma concentration in patients (80-280 nM), it is thought that the intracellular concentration of paclitaxel accumulated in MDA-MB-231 cells in vitro and in a tumor are similar, in view of a study conducted by Zasadil et al (7). Since MDA-MB-231-JYJ cells, the small round cells that survived treatment with paclitaxel, were much more proliferative and tumorigenic than MDA-MB-231 cells (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…The final concentration at the end of the establishment process of paclitaxel resistant cancer cells is far beyond its GI 50 concentration. A recent study has shown that patients treated with 175 mg/m 2 paclitaxel for 3 h had plasma concentrations ranging from 80-280 nM, and intratumoral concentrations of 1.1-9.0 ÂľM at 20 h following administration of the agent (7). These high intratumoral concentrations are due to the intracellular accumulation of paclitaxel.…”
Section: Introductionmentioning
confidence: 99%
“…In a landmark study using CENPE Ăž/ -mice, Cleveland and colleagues showed that CIN promotes tumorigenesis in tissues with low endogenous levels of aneuploidy (lung and lymphocytes), but is tumor suppressive in the liver, which displays high levels of endogenous segregation errors (Weaver et al 2007). Exploiting the tumor suppressive function of excessive CIN is the basis for using SAC inhibitors to target cancer cells and could contribute to the cytotoxic effect of paclitaxel (Janssen et al 2011a;Zasadil et al 2014;Drost et al 2015;Lee et al 2016). …”
Section: Determinants Of Cin Propagation Sustainable Versus Lethal Lementioning
confidence: 99%
“…This blocks the progression of mitosis. Further, a prolonged activation of the mitotic checkpoint triggers either an apoptosis or a reversion to the G-phase of the cell cycle without cell division (Zasadil et al, 2014). A big problem in the successful treatment with the taxanes is the appearance of the primary and acquired resistance, which has driven the search for alternative agents, such as epothilones (EPOxide, THIazoLe, ketONES), which could replace them (Smaglo and Pishvaian, 2014;Navarrete et al, 2015).…”
Section: Introductionmentioning
confidence: 99%